Effect of red meat, vegetable, tobacco, and alcohol consumption on national cancer mortality index: Data from 1989 to 2013 in 37 developed countries - Park, Myung-Bae (Frontiers in Nutrition, 2022)
This study aimed to examine the association between red meat (RM) and death from all types of cancer, as well as its association with the incidence of colon cancer in developed countries.We selected RM, vegetable, tobacco, alcohol consumption, and socioeconomic status as the dependent variables’ risk factors and performed ordinary least squares (OLS) and a fixed-effect model (FEM) analysis. Data from 1989-2013 for 37 Organization for Economic Cooperation and Development (OECD) countries. According to the FEM, cancer death had statistically significant associations with education level (Coef= -0.022, P=0.009), total health expenditure (Coef= -0.049, P=0.000), aging rate (Coef= -0.178, P=0.000), tobacco consumption (Coef= 0.096, P=0.000), RM consumption (Coef= 0.107, P=0.000), and vegetable consumption (Coef= -0.034, P=0.000). A similar trend was also observed in the 3 and 5-year lagged models. RM consumption also demonstrated a significantly positive association with the incidence of colon cancer in the OLS. According to the scatter plots and fitted lines based on the recommended allowance RM consumption, cancer deaths and incidence of colon cancer increased as consumption increased in the excess consumption group. Regarding vegetable consumption, cancer deaths and incidence of colon cancer decreased as consumption increased in the group exceeding the recommended allowance level. RM consumption was found to be higher than the recommended allowance level. RM consumption increased cancer deaths and the incidence of colon cancer. There is justification for public health interventions to limit RM consumption in major developed countries.